Analisis Penerapan Kode Etik Jurnalistik pada Harian Serambi Indonesia - Sari, Fitri Meliya (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2014)
The press was given the freedom to seek, cultivate and to spread the word that corresponds to the code of ethics of journalism to keep its integrity. This study aims to look at the implementation of the code of journalism ethics on crime news in Harian Serambi Indonesia. Using the content analysis method with a documentation technique that collects data in the form of criminal clipping. Analysis of the data using content analysis with a reliability test using the formula R. Holsty and reinforced by the formula Scott Pi, where the threshold of 0.75. And the results of reliability test CR - 1 and pi = 1, qualified to conduct this research. This means Harian Serambi Indonesia has implemented the Code of Journalism Ethics at writing crime news.